EFFECT OF PRODUCT DIFFERENCE AND PERCEPTION PRICE ON PURCHASE DECISION AT THE KESU GARU CHEESE SHOP, MEDAN - Safina, Wan Dian; Harahap, Dewi Sartika (Movere Journal, 2023)
This study aims to examine the effect of product differentiation and price perceptions on purchasing decisions at Kesu Garu II Cheese Shop in Medan. The method used is Quantitative. The problem of this research is Does Product Differentiation Affect the Purchase Decision of the Medan Kesu Cheese Shop, Does Price Perception Affect the Purchase Decision of the Medan Kesu Cheese Shop and Does Product Differentiation and Perceived Price Affect the Purchase Decision of the Medan Kesu Cheese Shop. The sample of this study consists of 95 people. using questionnaire or statement data collection techniques with statistical data analysis using SPSS. The results of this study indicate that there is a significant effect of partial differentiation with a positive value on purchasing decisions, this is consistent with the t-count value of 2,887 greater than t-table 1,665 (7,685 > 1,665) in a positive direction. There is a partial influence of price perceptions with a significance of 11,354 with a t-value of 2,897 greater than t-table 1,665 (11,354 > 2.021), with a positive effect. Based on the table obtained Fcount of 737,857 > from Ftable12,150 with a significant level of 0.000, then reject Ho (Accept H1) it is concluded that differentiation and price perception simultaneously (simultaneously) have a positive and significant effect on the decision to buy cheese. Thus the previous hypothesis (H1) is accepted. The magnitude of the influence of X1 and X2 on the Y variable is 97.6%.